Estudio de factibilidad para la ampliación del portafolio de productos de la empresa Limón & Limonada (2017)
The project is carried out in the city of Bogotá in 2016, is a feasibility study for the expansion of the product portfolio of the company Limón & Limonada, where an external and internal diagnosis of the organization is developed, a study of Markets to identify the demand for new production lines and the design of its production processes, providing growth opportunities for the company in the food and beverage industry.